Yes, I surely can.
We know that,
-6 = -6
i.e., 4 - 10 = 9 - 15
i.e., 4 - 10 + (25/4) = 9 - 15 + (25/4)
i.e., 2^2 - 2*2*(5/2) + (5/2)^2 = 3^2 - 2*3*(5/2) + (5/2)^2
i.e., (2 - 5/2)^2 = (3 - 5/2)^2
i.e., 2 - 5/2 = 3 - 5/2
i.e., 2 = 3
But it is obvious that there must be some error in the process depicted, 'coz we know that 2 can never be equal to 3. So, try to figure out the mistake in the prcess. Let me know when you've successfully figured it out.
2007-02-19 16:02:42
·
answer #1
·
answered by Kristada 2
·
0⤊
1⤋
The proof is in the pooding. LOL In my book 1 = 2 if the 2 items that make up the 2 are 1 unit. Making 2 = 1 hence 1 = 2.
Another example is 1 dog weighs 300 pounds and 2 other dogs weigh 150 pounds. The 1 dog is equal to the 2 other dogs. 1 = 2!
2007-02-19 15:51:53
·
answer #2
·
answered by mazaker2000 3
·
0⤊
0⤋
becuase 1 times 2 =2 and
2007-02-19 15:50:47
·
answer #3
·
answered by fjbelgrave 1
·
0⤊
0⤋
in case you defined a series of axioms in the previous the technique of proving 2=a million (that a large type of folk have shown above, so I shant repeat)then specific you may coach the fact. yet in prevalent algebraic arithmetic dividing via 0 isn't obtainable, it relatively is undefined. So relatively what you all have achieved is to define your very own good judgment rules and prooved 2=a million, however the evidence is improper and invalid below prevalent algebraic axioms.
2016-10-02 10:31:06
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Although there is a significant flaw in this logic, here it is:
a = b
a^2 = ab (multiply both sides by a)
a^2 - b^2 = ab - b^2 (subtract b^2 from both sides)
(a + b)(a - b) = b (a - b) (factor)
(a +b) = b (divide by (a-b)
2b = b (since a = b above)
2 = 1 (divide by b)
2007-02-19 15:58:48
·
answer #5
·
answered by Hokieman 2
·
0⤊
0⤋
1 is equal to 2 halves
2007-02-19 16:01:12
·
answer #6
·
answered by Manz 5
·
0⤊
0⤋
Yeah, sure... You are going to use algebra and at some point, are going to divide by (a-b) where both a and b are equal to 1; but that is called dividing by zero, and is never part of any real, valid proof.
2007-02-19 15:58:00
·
answer #7
·
answered by Vincent G 7
·
0⤊
0⤋
1) x = y
2) x^2 = xy (multiply both sides by x)
3) x^2 - y^2 = xy - y^2 (subtract y^2 from each side)
4) (x + y)(x - y) = y(x - y) (factor)
5) x + y = y (divide out (x - y))
6) 2y = y (substitute y for x from #1)
7) 2 = 1 (What do you think of that?!)
2007-02-19 15:55:09
·
answer #8
·
answered by deep 2
·
0⤊
1⤋
Suppose one does equal two
then I am one person.
The president of the USA is another person
Together we are two people.
Since two equals one then I am the president of the united states.
Now to put the world to rights.
2007-02-19 18:30:22
·
answer #9
·
answered by crazy_tentacle 3
·
0⤊
0⤋
I've seen same question on the TV show.
1=2 means people can't live without someone's help.
2007-02-19 15:51:23
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋